PENGARUH MODAL USAHA, LOKASI, DAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG SAYUR - Aprianis Eka Pratiwi; Yuana Mei Nanda Sari; Sulastri Rini Rindrayani (Universitas Tulungagung, 2023)
The market plays an important role in economic activity and economic development of a country, capital is one of the important factors in a production, a strategic location greatly influences income. the merchandise. This is due to the high level of competition among fellow traders. The aim of the study was to determine the effect of capital, location, and working hours on the income of vegetable traders at the Campurdarat People's Market, Tulungagung Regency, both simultaneously and partially, and to determine the effect of the independent variable that has the most dominant effect on the dependent variable. The research method used is quantitative research in the form of causal (influence), namely a relationship that influences two or more variables, and conducts field research (field research). The research design used is a case study design. The results showed that the multiple correlation coefficient was 0.878, meaning that between the modal variables, and l, the location of working hours and the traders' income variables showed a very strong relationship. The results of the t test show that partially the independent variable that has the greatest influence is location, with the acquisition of an Unstandardized Coefficients value of 0.779, a tcount value of 5.546, and a significance value of 0.000. The results of the F test value of Fcount = 34.704 and sig. 0.000 while Ftable = 2.92 so that the value of Fcount is greater than Ftable or less than the probability value of 0.05 (0.000 <0.05), then H0 is rejected and Ha is accepted. So, from the results of multiple regression analysis and F test it can be seen that capital (X1), location (X2), working hours (X3) have a simultaneous and significant effect on trader income (Y). Business capital has a negative but significant effect on merchant income. In the working hours variable, the significance value is 0.099 greater than 0.05, this indicates that working hours have no significant effect on merchant income.